Reconstruction of an 8-lead surface ECG from two subcutaneous ICD vectors. (1st June 2017) - Wilson, David G; Cronbach, Peter L; Panfilo, D; Greenhut, Saul E; Stegemann, Berthold P; Morgan, John M
Abstract: Introduction: Techniques exist which allow surface ECGs to be reconstructed from reduced lead sets. We aimed to reconstruct an 8-lead ECG from two independent S-ICD sensing electrodes vectors as proof of this principle. Methods: Participants with ICDs ( N  = 61) underwent 3 minute ECGs using a TMSi Porti7 multi-channel signal recorder (TMS international, The Netherlands) with electrodes in the standard S-ICD and 12-lead positions. Participants were randomised to either a training ( N  = 31) or validation ( N  = 30) group. The transformation used was a linear combination of the 2 independent S-ICD vectors to each of the 8 independent leads of the 12-lead ECG, with coefficients selected that minimized the root mean square error (RMSE) between recorded and derived ECGs when applied to the training group. The transformation was then applied to the validation group and agreement between the recorded and derived lead pairs was measured by Pearson correlation coefficient ( r ) and normalised RMSE (NRMSE). Results: In total, 27 patients with complete data sets were included in the validation set consisting of 57, 888 data points from 216 full lead sets. The distribution of the r and NRMSE were skewed. Mean r  = 0.770 (SE 0.024), median r  = 0.925. NRMSE mean = 0.233 (SE 0.015) median = 0.171. Conclusions: We have demonstrated that the reconstruction of an 8-lead ECG from two S-ICD vectors is possible. If perfected, the ability to generate accurate multi-lead surface ECG data from an S-ICD would potentially allow recording and review of clinical arrhythmias at follow-up.